2020
DOI: 10.1021/acs.est.0c02197
|View full text |Cite
|
Sign up to set email alerts
|

Copper and Gold Nanoparticles Increase Nutrient Excretion Rates of Primary Consumers

Abstract: Freshwater ecosystems are exposed to engineered nanoparticles through municipal and industrial wastewater-effluent discharges and agricultural nonpoint source runoff. Because previous work has shown that engineered nanoparticles from these sources can accumulate in freshwater algal assemblages, we hypothesized that nanoparticles may affect the biology of primary consumers by altering the processing of two critical nutrients associated with growth and survivorship, nitrogen and phosphorus. We tested this hypoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 91 publications
1
14
0
Order By: Relevance
“…46 The use of isotopically labeled ENMs shows a great potential for detecting and discerning ENMs apart from the natural background at realistic contamination concentrations and can be applied to a wide range of metal-, metalloid-, or carbon-based ENMs. For instance, similar techniques enabled the detection of 109 Agenriched Ag-ENMs 58 or multi-isotopically labeled 111 Cd 77 Se/ 68 ZnS QDs 59,60 at concentrations as low as ng L −1 in complex matrices. Furthermore, understanding the isotopic fingerprint of ENMs can help distinguish natural from manufactured ENMs and even the synthetic methods and manufacturers of engineered ENMs.…”
Section: Large Panel Of Enm Environmentalmentioning
confidence: 99%
See 1 more Smart Citation
“…46 The use of isotopically labeled ENMs shows a great potential for detecting and discerning ENMs apart from the natural background at realistic contamination concentrations and can be applied to a wide range of metal-, metalloid-, or carbon-based ENMs. For instance, similar techniques enabled the detection of 109 Agenriched Ag-ENMs 58 or multi-isotopically labeled 111 Cd 77 Se/ 68 ZnS QDs 59,60 at concentrations as low as ng L −1 in complex matrices. Furthermore, understanding the isotopic fingerprint of ENMs can help distinguish natural from manufactured ENMs and even the synthetic methods and manufacturers of engineered ENMs.…”
Section: Large Panel Of Enm Environmentalmentioning
confidence: 99%
“…In estuarine ecosystems, evidence of DNA damage and oxidative stress in clams exposed to Cu- and Ag-ENMs is attributed to the uptake of aggregated ENMs containing redox active metals . In freshwater ecosystems, ENM contamination led to behavioral alterations of bivalve filtering capacity (Ce-ENM) and mollusc excretion rates (Au- and Cu-ENMs). Ce-ENMs also induced oxidative stress to snails and genotoxic effects in amphibian larvae, , linked to the uptake of aggregated ENMs and the subsequent bioreduction of Ce­(IV) in Ce­(III). , In these studies, citrate-coated Ce-ENMs were less aggregated and more bioavailable but caused lower oxidative stress, likely because of the antioxidant properties of the organic ligands…”
Section: Environmental Risk For Aquatic Ecological Nichesmentioning
confidence: 99%
“…Additionally, the sediment could act as a sink for CuO-NP and furthermore have negative effects on, for example, the abundance and bioaccumulation of sediment dwelling organisms like Gastrotricha (e.g., Chaetonotus ), Annelida (e.g., Lumbriculus ), and Mollusca (e.g., Lymnea, Physella ). ,,,, In this process, CuO-NP can be transformed more slowly and in a different ration to organic Cu-sulfides and NOM-Cu bound copper compared to added ions (e.g., Cu­(NO 3 ) 2 ) resulting in different fate processes. , Avellan et al demonstrated that the persistence and dissolution of NP affects their mobility and accumulation in different compartments. Nanoparticles can also be remobilized and thus become bioavailable and enter the food web, which could subsequently lead to a trophic transfer. , The bioavailability of nanoparticulated Cu in fish was twice of that of CuSO 4 .…”
Section: Discussionmentioning
confidence: 99%
“…Spiders and mosquitofish were processed individually in the same manner. Digestions followed a previously published protocol. , Cu and Au were quantified using an Agilent 7900 ICP-MS generally following U.S. EPA Method 6020A . All analytical runs included reagent blanks, fortified water and tissue-mixed spike recovery samples, and standard reference material recovery (NIST 1643e).…”
Section: Methodsmentioning
confidence: 99%
“…Nutrients did not have any effect on metal accumulation into various mesocosm compartments, but we observed interactions between nutrients and nanoparticles resulting in increased primary productivity. 5,40 Here, we studied the interactive effects of additions of copper hydroxide nanoparticles (CuNPs) or gold nanoparticles (AuNPs) and nutrient enrichment on the rate of insect emergence, metal accumulation in adult insects, and flux of metals into riparian spiders in a 9-month wetland mesocosm experiment. We added CuNPs found in a commercially available nanopesticide at the application dose to investigate particle and biotic interactions likely to be occurring in aquatic ecosystems.…”
Section: ■ Introductionmentioning
confidence: 99%